2011
DOI: 10.1016/j.febslet.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Substrate positioning in chitinase A, a processive chito-biohydrolase fromSerratia marcescens

Abstract: a b s t r a c tThe contributions of the -3 subsite and a putative +3 subsite to substrate positioning in ChiA from Serratia marcescens have been investigated by comparing how ChiA and its -3 subsite mutant W167A interact with soluble substrates. The data show that Trp -GlcNAc stacking in the -3 subsite rigidifies the protein backbone supporting the formation of the intermolecular interaction network that is necessary for the recognition and positioning of the N-acetyl groups before the -1 subsite. The +3 subsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…lignolyticus SCF1. Phylogenetic analysis has shown that ECENHK_07430 and the synthetic Enterobacter chitinases are associated with the well-characterized Chitinase A in Serratia marcescens [62,63] (Figure 5), which has been demonstrated to control several important plant pathogenic fungi including Botrytis spp., Rhizoctonia solani, Fusarium oxysporum f. sp. cyclaminis and Sclerotinia spp.…”
Section: Resultsmentioning
confidence: 99%
“…lignolyticus SCF1. Phylogenetic analysis has shown that ECENHK_07430 and the synthetic Enterobacter chitinases are associated with the well-characterized Chitinase A in Serratia marcescens [62,63] (Figure 5), which has been demonstrated to control several important plant pathogenic fungi including Botrytis spp., Rhizoctonia solani, Fusarium oxysporum f. sp. cyclaminis and Sclerotinia spp.…”
Section: Resultsmentioning
confidence: 99%
“…Although the Phe and Trp residues confer aromaticity, the bulky side chain (increased surface area) of Trp facilitates more interactions with the incoming substrate (14). The Trp also might assist in correct positioning and guiding of the sugar molecule into the active site (37). The increased TG by F64W for 60 min and then a gradual decrease may be because the sugar molecules with higher DP will possibly have more interactions with the Trp residue.…”
Section: Relative Tg Activitymentioning
confidence: 99%
“…The situation beyond subsite +2 for HCHT, AMCase, and ChiA, is less clear. Still, chito-oligosaccharide degradation by ChiA clearly show substrate binding affinity in a subsite +3 that has been linked to its endo-activity [21].…”
Section: Introductionmentioning
confidence: 99%